2002
DOI: 10.1021/jo020114o
|View full text |Cite
|
Sign up to set email alerts
|

Dithienylethenes with a Novel Photochromic Performance

Abstract: Dithienylethenes with low decoloration quantum yields and thermal reversibility at high temperature above 100 degrees C were prepared. Introduction of bulky alkoxy substituents at 2- and 2'-positions of the thiophene rings strongly suppressed the cycloreversion quantum yields. The quantum yields were lower than 10(-3), and the photogenerated color remained stable enough under room light. On the other hand, the bulky alkoxy substituent decreased the thermal stability of the colored closed-ring isomers at high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(92 citation statements)
references
References 22 publications
0
92
0
Order By: Relevance
“…Diarylethenes bearing a pyrazole unit have a relatively high cycloreversion quantum yield [27], whereas dithienylethenes bearing bulky alkoxy groups at 2-and 2 0 -positions of the thiophene rings have a very small cycloreversion quantum yield [28]. Kawai et al reported the triangular terthiophene derivatives which showed reversible photochromic reactions with high cyclization quantum yields [29].…”
Section: Introductionmentioning
confidence: 99%
“…Diarylethenes bearing a pyrazole unit have a relatively high cycloreversion quantum yield [27], whereas dithienylethenes bearing bulky alkoxy groups at 2-and 2 0 -positions of the thiophene rings have a very small cycloreversion quantum yield [28]. Kawai et al reported the triangular terthiophene derivatives which showed reversible photochromic reactions with high cyclization quantum yields [29].…”
Section: Introductionmentioning
confidence: 99%
“…This unstable blue-colored closed ring returns to the colorless open-ring form with a half life time of 37 s, which requires a thermal fading activation energy of 32.5 kJ mol −1 [68]. Furthermore, the introduction of bulky substituents at the reacting positions of dithenylethenes decreases the thermal stability of the closed-ring isomers at higher temperatures [69]. An extraordinarily high thermal stability of t 1/2 = 4.7 × 10 5 years was shown for a closed-ring isomer of 1,2-bis(5-methyl-2-phenylthiazol-4-yl) perfluorocyclopentene at 30 • C [70].…”
Section: Diarylethenesmentioning
confidence: 99%
“…In previous literatures, numerous photochromic properties of diarylethene derivatives have been carried out (Yumoto, K. et al 2008, Morimitsu, K. et al 2002. However, there are few publications reported photochromic unsymmetrical hybrid diarylethene derivatives with methoxyphenyl moieties.…”
Section: Introductionmentioning
confidence: 99%